The hub-and-spoke organization design revisited: a lifeline for rural hospitals - James K. Elrod; John L. Fortenberry (BMC, 2017)
Abstract Background Characterized by declining populations, high poverty, reduced employment opportunities, and high numbers of uninsured residents, rural communities pose significant challenges for healthcare providers desirous of addressing these medically underserved areas. Such difficult environments, in fact, have forced the closure of many rural hospitals across America, with scores facing the same threat, compelling intensive efforts to identify pathways which will yield an improved future. Discussion Collaborations with stronger urban or suburban healthcare institutions offer a prudent avenue for rural hospitals to continue serving their patients. Such relationships can be structured in many different ways, but Willis-Knighton Health System found that its use of the hub-and-spoke organization design set the stage for the institution to cast a vital lifeline to neighboring rural hospitals, affording the relatively seamless integration and assimilation of partner facilities into its network, ensuring continuity of services in remote regions. This article supplies an overview of the hub-and-spoke network and discusses Willis-Knighton Health System's use of it to facilitate the establishment of productive partnerships with rural hospitals. Conclusions The delivery of healthcare services in rural environments is essential, but with small community hospitals increasingly being under threat, the outlook is not particularly attractive. Partnerships with better positioned healthcare entities offer significant hope, but care must be taken to structure these arrangements optimally. Willis-Knighton Health System found utility and value in its hub-and-spoke organization design, with the insights presented in this account potentially offering a pathway for others to follow as they go about addressing the healthcare needs of rural populations.